Simplify. Remove grouping symbols and combine like terms. A) 5[3a-2a(3a+6b)+6a^2]

### 2 Answers | Add Yours

`5[3a-2a(3a+6b)+6a^2]`

`= 5[3a-6a^2-12ab+6a^2]`

`= 5(3a-12ab)`

`= 15a-60ab`

*So the answer is;*

`5[3a-2a(3a+6b)+6a^2] = 15a-60ab`

`5[3a-2a(3a+6b)+6a^2]`

`5(3a-6a^2-12ba+6a^2)` you can distribute the 5 then combine like terms or combine like terms then distribute the 5

5(3a-6a^2+6a^2-12ba)

5(3a-12ba)

15a-60ba

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes